KEABSAHAN PERATURAN DAERAH DALAM RANGKA PENYELENGGARAAN OTONOMI DAERAH - Akhmad Nikhrawi Hamdie (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
The existence of regional authority to make regional regulations for their own region based on the principle of regional autonomy does not mean that the regional government is sovereign, because supervision and supreme power still remain in the hands of the central government. According to Law Number 32 Year 2004 regarding Regional Government there are two signs that should not be violated by regional regulations, namely: (a) contrary to public interest, and / or (b) contrary to higher laws and regulations. Regarding the criterion is against the public interest, Law Number 32 Year 2004 does not regulate it clearly and specifically. However, Article 4 Paragraph (4) of Kepmendagri Number 41 Year 2001 concerning Technique of Represive Control of Regional Policies which is actually a regulation of the implementation of Law Number 22 Year 1999, declared the general interest as meant in Article 4 paragraph (3) letter a, Or customs prevailing in an area, such as religious norms, customs, culture, and morals, as well as things that burden the public and incur high economic costs. Meanwhile, the higher laws and regulations as referred to in Article 4 paragraph (3) b, covering the 1945 Constitution, MPR Decrees, Laws, Government Regulations, Presidential Decrees, and Ministerial Decrees.